EFFECTS OF PSYCHOLOGICAL FACTORS AND ACADEMIC SUPPLIERS ON INDONESIAN STUDENTS’ ACADEMIC RECORDS AND CAREER - Prabandari, Sri Palupi (International Journal of Supply Chain Management, 2020)
Students? academic records are an important part of students learning life. Academic records provide awareness to the observer about a student?s performance and forethought about the student?s future planning. Hence, insight against the factors that impact on academic records is very necessary. Although, there is a list of factors involved in the matter, however, psychological factors such as educational organization and teaching method play an essential role to build a better or junk academic record by a student. The current study has depicted the role of both the educational organization and teaching method, how these two can help an Indonesian student to make outstanding and exceptional academic records, which are necessary for the students to build a strong academic career.  According to this study, a strong academic career is only possible when there are consistency and continuity of very good academic records for each class and course passed by a student. Statistical software; Partial Least Square was used for data analysis. Hence, for primary data collection, a survey was accomplished. Data analysis was completed to obtain final results based on the 395 responses received from the respondents of this study.  Besides, our study provides a significant evidence for the fact that academic suppliers like family, student suppliers, and faculty suppliers are positively impacting on academic career of the students.